Ibu Obesitas berpengaruh pada Obesitas Anak (Permodelan Pencegahan Dini Obesitas Anak) - Wiyono, Sugeng; Muntikah, Muntikah; Miranti, Miranti (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
The Childhood Obesity Early Prevention Modelling study aims to identify factors influencing childhood obesity and develop an early prevention model. Childhood obesity is a significant health problem as it can increase the risk of future chronic diseases, such as diabetes and cardiovascular disease. This study focused on primary school-aged children, as this is a critical period in the development of dietary and physical habits. This study used a case-control design with surveys of parents and children to collect data on eating habits, physical activity, and environmental factors such as parenting and access to healthy food. In addition, anthropometric measurements were taken to determine children's nutritional status based on body mass index (BMI/U). The study involved case and control samples in terms of gender and age of 28 children each. Khi Kuadrat Test and Multiple Logistic Regression Test were used to test the hypothesis. The results of the study are expected to identify the main risk factors contributing to obesity. It is concluded that children whose mothers are obese have a 14.504 times higher chance of suffering from obesity compared to children of normal-weight mothers after controlling for the variable nutritional status of the father, who is also obese. The model will include interventions in nutrition education, increased physical activity, and support strategies for parents in managing their children's diets. In conclusion, this study provides a foundation for designing an evidence-based obesity prevention program in Jagakarsa District. It is hoped that the early prevention model generated from this study can be replicated in other areas with similar characteristics to reduce the prevalence of childhood obesity.